Heterogeneity and Spatial Distribution of Intravertebral Trabecular Bone Mineral Density in the Lumbar Spine Is Associated With Prevalent Vertebral Fracture. (16th January 2020) - Kaiser, Jarred; Allaire, Brett; Fein, Paul M; Lu, Darlene; Adams, Alexander; Kiel, Douglas P; Jarraya, Mohamed; Guermazi, Ali; Demissie, Serkalem; Samelson, Elizabeth J; Bouxsein, Mary L; Morgan, Elise F
ABSTRACT: The spatial heterogeneity in trabecular bone density within the vertebral centrum is associated with vertebral strength and could explain why volumetric bone mineral density (vBMD) exhibits low sensitivity in identifying fracture risk. This study evaluated whether the heterogeneity and spatial distribution of trabecular vBMD are associated with prevalent vertebral fracture. We examined the volumetric quantitative computed tomography (QCT) scans of the L3 vertebra in 148 participants in the Framingham Heart Study Multidetector CT study. Of these individuals, 37 were identified as cases of prevalent fracture, and 111 were controls, matched on sex and age with three controls per case. vBMD was calculated within 5‐mm contiguous cubic regions of the centrum. Two measures of heterogeneity were calculated: (i) interquartile range (IQR); and (ii) quartile coefficient of variation (QCV). Ratios in the spatial distributions of the trabecular vBMD were also calculated: anterior/posterior, central/outer, superior/mid‐transverse, and inferior/mid‐transverse. Heterogeneity and spatial distributions were compared between cases and controls using Wilcoxon rank sum tests and t tests and tested for association with prevalent fractures with conditional logistic regressions independent of integral vBMD. Prevalent fracture cases had lower mean ± SD integral vBMD (134 ± 38 versus165 ± 42 mg/cm 3, p < .001), higher QCV (0.22 ± 0.13 versus 0.17 ± 0.09, p = .003), and lower anterior/posterior rBMD (0.65 ± 0.13 versus 0.78 ± 0.16, p < .001) than controls. QCV was positively associated with increased odds of prevalent fracture (OR 1.61; 95% CI, 1.04 to 2.49; p = .034), but this association was not independent of integral vBMD ( p = .598). Increased anterior/posterior trabecular vBMD ratio was associated with decreased odds of prevalent fracture independent of integral vBMD (OR 0.38; 95% CI, 0.20 to 0.71; p = .003). In conclusion, increased trabecular vBMD in the anterior versus posterior centrum, but not trabecular vBMD heterogeneity, was associated with decreased risk of prevalent fracture independent of integral vBMD. Regional measurements of trabecular vBMD could aid in determining the risk and underlying mechanisms of vertebral fracture. © 2019 American Society for Bone and Mineral Research.